Kinematics of Articulated Planar Linkages - Zhao, Jing-Shan; Wei, Song-Tao (Frontiers in Mechanical Engineering, 2021)
This paper proposes a kinematics algorithm in screw coordinates for articulated linkages. As the screw consists of velocity and position variables of a joint, the solutions of the forward and inverse velocities are the functions of position coordinates and their time derivatives. With the velocity solution, we obtain the displacements of all joints through one-order integration and the accelerations of the joints via one-order differential. Both the forward and the inverse kinematics have the similar calculation process in this method. Through examples of planar open-chain linkage, single closed-chain linkage and multiple closed-chain linkage, the kinematics algorithm is validated. It is particularly fit for developing numerical programmers for forward and inverse kinematics in the same procedures, including the velocity, displacement and acceleration which provide the fundamental information for dynamics of the linkage.